A fuzzy control system for energy‐efficient wireless devices in the Internet of vehicles. Issue 4 (6th January 2021) - Collotta, Mario; Ferrero, Renato; Giusto, Edoardo; Ghazi Vakili, Mohammad; Grecuccio, Jacopo; Kong, Xiangjie; You, Ilsun
Abstract: Embedded systems are common in the Internet of Things domain: their integration in vehicles and mobile devices is being fostered in the Internet of vehicles (IoV). IoV has direct applications on intelligent transportation systems and smart cities. Besides basic requirements, such as ease of installation, cost‐effectiveness, scalability, and flexibility, IOV applications need to guarantee energy‐efficient and good‐quality communication. In fact, IoV implementations are commonly based on wireless nodes, which rely on a limited energy source; therefore, an efficient communication among the nodes is desirable to prolong the lifetime of the devices. In particular, the alternation of active and sleep states and the regulation of the transmission power represent two common approaches to save energy. Based on this strategy, an effective fuzzy control system is presented in the paper to manage power consumption and quality of services of IoV applications. Two fuzzy controllers increase the battery life while keeping a good throughput to workload ratio. This technique has been simulated with two leading technologies in IoV: IEEE 802.11b/g/n and IEEE 802.11p. Experimental results show a network lifetime improvement ranging from 30% to 40%, according to the adopted medium access control protocol.